2018
DOI: 10.1186/s40169-018-0209-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial biofilm formation inside colonic crypts may accelerate colorectal carcinogenesis

Abstract: Background Research in the field of relation between microbes and colorectal carcinogenesis has gained increasing interest in past years. Recently, link between microbial biofilm and carcinogenesis in colon was demonstrated by several authors indicating that biofilm not only is a key player in carcinogenesis, but also may contribute to the understanding of side-specific colon cancer—right sided colon cancer versus left sided. In this article, we briefly highlight the major findings of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…In humans, bacterial biofilms and mucus invasive bacteria have recently been reported to be a characteristic feature of right‐sided tumors 5,16,17 . Biopsies of the normal‐appearing mucosa from these patients also display biofilms, which are uncommonly seen in patients with distal tumors or healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, bacterial biofilms and mucus invasive bacteria have recently been reported to be a characteristic feature of right‐sided tumors 5,16,17 . Biopsies of the normal‐appearing mucosa from these patients also display biofilms, which are uncommonly seen in patients with distal tumors or healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of quorum sensing regulates the process of biofilm formation, which will further enable the bacteria to persist in the host cells and escape the host defense immune system [ 112 ]. In addition, the biofilm formation can result in the progression of colon and colorectal carcinogenesis [ 113 ]. Biofilm can be exploited as potential anti-cancer agents due to its ability to deliver therapeutics and to curb the spread of metastatic tumors.…”
Section: Mechanism Of Tumor Suppressionmentioning
confidence: 99%
“…Besides from the vermiform appendix, presence of mixedspecies biofilms in the healthy gut mucosa is still debated (Tytgat et al, 2019), though some studies have shown bacterial biofilms in close proximity to the epithelial lining, but only in the appendixes (Palestrant et al, 2004). Presence of biofilms in the colonic crypts has been described for intestinal diseases such as colorectal cancer (Raskov et al, 2018) and visualization of mixed-species biofilms has likewise been reported (Dejea et al, 2014).…”
Section: Gut Microbiotamentioning
confidence: 99%